Environmental and health impacts of disposable sanitary pads: A systematic literature review (Research, Society and Development, 2025)
Demand for menstrual products has grown alongside the global female population; convenience and affordability have established the disposable pad as the predominant choice, but its effects extend beyond the individual, impacting public health, society, and the environment. To address these impacts, this article aims to analyze the production, use, and disposal of menstrual pads, considering their environmental, health, and social implications. An integrative literature review was conducted using the PubMed and ScienceDirect databases, followed by analysis in Google Sheets and organization according to the PRISMA (2020) protocol. The selected articles were analyzed for correlation using VOSviewer® software and for the construction of a cluster map. The life cycle of disposable pads constitutes an intersectoral problem, characterized by plastic pollution, health risks associated with chemical compounds such as phthalates and PFAS, and social inequalities manifested in period poverty. There is a need to implement public policies that regulate harmful substances, foster sustainable alternatives, and promote menstrual health education, ensuring dignity, equity, and sustainability.